2020
DOI: 10.1016/j.bj.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia for pediatric refractory status epilepticus May Ameliorate post-status epilepticus epilepsy

Abstract: Background To compare the clinical characteristics and outcomes of pediatric patients with refractory status epilepticus (RSE) and super-refractory status epilepticus (SRSE) who received therapeutic hypothermia (TH) plus anticonvulsants or anticonvulsants alone. Methods Two-medical referral centers, retrospective cohort study. Pediatric Intensive Care Unit (PICU) at Taoyuan Chang Gung Children's hospital and Kaohsiung Chang Gung Memorial Hospital. We reviewed the medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Furthermore, in a retrospective case series, 11 children with RSE treated with hypothermia had a decrease of seizure duration and showed improved long‐term outcomes compared to those without hypothermia. However, the specific effect of hypothermia on seizures in FIRES was difficult to ascertain; therefore, any definitive conclusions are difficult to draw 105 . A review of case series of SRSE in adults and children found hypothermia to be effective in controlling seizures in 82% of patients irrespective of their etiology.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in a retrospective case series, 11 children with RSE treated with hypothermia had a decrease of seizure duration and showed improved long‐term outcomes compared to those without hypothermia. However, the specific effect of hypothermia on seizures in FIRES was difficult to ascertain; therefore, any definitive conclusions are difficult to draw 105 . A review of case series of SRSE in adults and children found hypothermia to be effective in controlling seizures in 82% of patients irrespective of their etiology.…”
Section: Resultsmentioning
confidence: 99%
“…By protecting the BBB integrity and reducing pro-inflammatory cytokines, TH may work toward the control of SE [11]. In a retrospective Taiwanese [17] study, seven patients with FIRES were managed for a few days with hypothermia (34-35°) and showed a significantly shorter duration of seizures, a better long-term outcome, and lower incidence of later refractory chronic epilepsy. Complications of hypothermia were bradycardia and electrolyte imbalance.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…To note, this issue contains additionally two original articles by the author's department, reporting encouraging first results regarding the use of TTM for the treatment of paediatric refractory status epilepticus [ 37 ], as well as the predictive value of seizure patterns during rewarming after TTM in neonates with hypoxic-ischaemic encephalopathy [ 38 ].…”
Section: Also In This Issuementioning
confidence: 99%
“…Here, Hsu et al. from the above-mentioned department conducted a retrospective cohort study on paediatric patients with refractory status epilepticus (RSE) and super-refractory status epilepticus (SRSE) [ 48 ], who received either anticonvulsants alone, or in combination with therapeutic hypothermia (TH) [ 37 ], for the purpose of comparing their clinical characteristics and outcomes.…”
Section: Also In This Issuementioning
confidence: 99%